(untitled) (Research, Society and Development, 2022)
Introduction: nutritional status is important in the progress of hospitalized patients, as nutritional deficits can increase length of stay and morbidity and mortality. Objectives: to know the nutritional status of hospitalized children and adolescents and to compare anthropometric parameters with subjective tools. Methods: observational, cross-sectional, prospective, analytical study in patients aged 29 days to 18 years, admitted to the pediatric ward of Hospital e Maternidade Santa Isabel (Aracaju-SE) between January and July 2021. An anthropometric assessment was carried out and subjective tools were applied, Screening Tool Risk on Nutritional Status and Growth (STRONGkids) and Subjective Global Nutrition Assessment (SGA), in the first 48 hours after admission. Results: consisted of 235 children and adolescents, 54% were male and 46% female. The age group of 29 days – 2 years (69.7%) prevailed. The mean length of hospital stays (5.2 days). Preponderant clinical diagnoses were respiratory diseases (60%) and urinary tract infection (13.70%). The predominant nutritional diagnosis, according to the body mass index (BMI) was normal weight (49.33%), as well as by the arm muscle circumference (AMC) (82.55%). STRONGkids showed moderate and high nutritional risk (64.25%). In SGA, moderate (15.75%) and severe (6.60%) malnutrition. There was statistical significance between SGA and BMI/age (p=0.032), SGA and height/age (p<0.001), SGA and AMC of (p=0.024). There was no relevant association between STRONGkids and anthropometry. Conclusion: there is nutritional risk during hospitalization and STRONGKids is unique in this assessment due to its greater sensitivity. The use of SGA is suggested in association with anthropometry and global analysis.